Educação bilíngue para surdos : um estudo acerca de práticas de letramento crítico com alunos surdos usuários da Língua Brasileira de Sinais - Cruz, Renata Cristina Vilaça (2016)
At a time when the issue of the inclusion of hearing-impaired students in regular schools has been discussed, it becomes necessary to reflect upon the relevance of a recurrent educational process in schools specialized in education for the hearing-impaired: the bilingual schools. Such institutions, still scarce in Brazil, offer an oriented and specialized education to hearing-impaired children and adolescents, since they have the Brazilian Sign Language as a language of instruction in all subjects, and the Portuguese written language as an additional language, which gives them the bilingual status. This research aims to investigate how the practices developed in my Portuguese classes in a bilingual school have contributed to the development of student‟s literacy, specifically the Critical Literacy (STREET, 1985, 1990, 1998), in two classes of hearing-impaired students enrolled in the final grades of elementary school. It is a qualitative, ethnographic research, which uses the triangulation system for analyzing data: (i) the pedagogical sequences; (ii) the students‟ activities and (iii) the teacher‟s and students‟ written accounts registered as field notes. Through the intersection of the data, this work evaluates whether students have achieved some level of Critical Literacy, and what kind of collaboration and/or activity is relevant during this process. This research is justified by the need to evaluate practices at bilingual schools that, although supported by current law in Brazil, are still a minority whose work is still not acknowledged or valued. The results show that activities using real texts of different genres can contribute to the development of Critical Literacy, and also to dynamic classes, with discussions about relevant topics to society in Sign Language. Also, activities that encourage students to do research and that provide to the hearing-impaired student, the understanding of the real usefulness of Portuguese as an instrument for the social inclusion of the hearing-impaired providing opportunities for them to change their social position can collaborate to this process.